Performance study on release behaviour of controlled release and water retention fertilizer coated with superabsorbent polymer-biochar incorporation - Nureen, Noordin (2020)
Superabsorbent polymer (SAP) had been gaining popularity on its use in agriculture. Its ability to absorb vast amount of water and retaining it for a period of time, proves to be beneficial to maintain soil moisture. In practices, only 30-40% of the fertilizer was absorb by plants while the rest are leached out and sometimes remain in the soil, creating environmental problem. The application of SAP with organic materials such as biochar as coating could control the nutrient release of fertilizer, and retaining water content. This helps reduces consumption of fertilizer and watering frequency. The first objective of this study is to study the elemental composition and yield of biochar, converted via pyrolysis method. The second one is to optimize the synthesis of SAP-biochar as coatings for controlled release water retention (CRWR) fertilizer. Lastly, is to study the nutrient release performance of SAP-biochar as coatings for CRWR fertilizer in soil. In this study, the agro waste of empty fruit bunch was utilized to produce biochar via pyrolysis. The pyrolysis temperature is varied at 250⁰C and 350⁰C. In the second objective, the design of experiment was carried out to optimize the water absorbency properties of SAPbiochar using STATISTIKA where the parameters chosen are the amount of Methylenebis- acrylamide (MBA) used, concentration of Acryl Amide (AM) and percentage of biochar. The SAP-biochar was prepared via graft co-polymerization method. Based on STATISTIKA analysis, the most favourable condition by synthesizing SAP-biochar via graft-co polymerization method is at 123.44 g/g operated at 5.87mol/L of AM, 0.046g of MBA and 0.23% biochar weight percentage. The performance of the CRWR fertilizer coated with SAP-biochar was characterized in terms of nutrient release and water retention behavior. In this part, the leachates of CRWR fertilizer which tested on soil were collected in order to determine the nutrient present in every 3 days for 30 days. The results for nutrient release and water retention behavior showed that the presence of SAP-biochar as coatings was acted as a barrier. The coatings helps in slowing down the release of nutrient and retaining water content. The presence of biochar, as expected could influence the release of nutrient due to the properties of biochar, which are able to hold nutrients in the soil.